Identification of potential risk factors for lower limb injuries in female team-sport athletes: a prospective cohort study - Almousa, S.; Mullen, R.; Williams, K.; Bourne, M.; Williams, M. (Science and Medicine in Football, 2024)
Objectives: The purpose of this prospective cohort study was to assess the associations between lower limb injuries in female team-sport athletes and a number of factors. The potential risk factors explored included (1) lower limb strength, (2) history of life-event stress, (3) family history of ACL injuries, (4) menstrual history, and (5) history of oral contraception use. Methods: One hundred and thirty-five female athletes aged between 14 and 31 years (mean: 18.8 ± 3.6 years) from rugby union (n = 47), soccer (n = 72), and netball (n = 16) volunteered to participate in this study. Demographics, history of life-event stress, injury history and baseline data were obtained prior to the competitive season. The following strength measures were collected: isometric hip adductor and abductor strength, eccentric knee flexor strength and single leg jumping kinetics. Athletes were then followed for 12 months, and all lower limb injuries sustained were recorded. Results: One hundred and nine athletes provided one-year follow-up injury data, of whom, 44 suffered at least one lower limb injury. All athletes who reported high scores for negative life-event stress sustained lower limb injuries. Non-contact lower limb injury was positively associated with weak hip adductor strength (OR: 0.88; 95%CI: 0.78-0.98; p = 0.017), and between-limb adductor (OR: 5.65; 95%CI: 1.61-19.7.; p = 0.007) and abductor (OR: 1.95; 95%CI: 1.03-3.71; p = 0.039) strength asymmetries. Conclusion: History of life event stress, hip adductor strength, and between-limb adductor and abductor strength asymmetries offer potential novel avenues for investigating injury risk factors in female athletes.